Roles and new Insights of Macrophages in the Tumor Microenvironment of Thyroid Cancer - Liu, Qi; Sun, Wei; Zhang, Hao (Frontiers in Pharmacology, 2022)
Abstract: Although most thyroid cancers have a good and predictable prognosis, the anaplastic, medullary, and refractory thyroid cancers still prone to recurrence and metastasis, resulting in poor prognosis. Although a number of newly developed targeted therapies have begun to be indicated for the above types of thyroid cancer in recent years, their ability to improve overall survival remain hindered by low efficacy. As the largest component of immune cells in tumor microenvironment, tumor-associated macrophages play a key role in the invasion and metastasis of thyroid cancer. There is much evidence that the immune system, tumor microenvironment and cancer stem cell interactions may revolutionize traditional therapeutic directions.Tumor-associated macrophages have been extensively studied in a variety of tumors, however, research on the relationship between thyroid cancer and macrophages is still insufficient. In this review, we summarize the functions of tumor-associated macrophages in different types of thyroid cancer, their cytokines or chemokines effect on thyroid cancer and the mechanisms that promote tumor proliferation and migration. In addition, we discuss the mechanisms by which tumor-associated macrophages maintain the stemness of thyroid cancer and potential strategies for targeting tumor-associated macrophages to treat thyroid cancer.